Estudo computacional do deslocamento de fluidos em tubulações na etapa de comissionamento das linhas de produção de petróleo offshore - Silva, Rafaella Casado (2022)
The importance of oil in the current scenario is related to its application both in the energy sector and in countless other products, such as plastic, fibers and rubbers. Petroleum is defined as a mixture naturally formed by hydrocarbons and sulfur, nitrogen and oxygenated organic derivatives, among others. Within the oil industry, production stoppage on offshore platforms can cause problems related to blocked flow of the production line due to the presence of highly viscous oil, which makes it difficult to restart the plant. Fluid displacement by flushing is one of the solutions applied in this situation and consists of pumping a fluid into the flow line with the intention of cleaning the oil. Thus, the present case study aimed to use computational fluid dynamics (CFD) to investigate the flow and cleaning time of an 8.15 m long acrylic test section with an internal diameter of 26 mm. In addition, it was also possible to validate the best turbulence model according to the conditions analyzed. For this, two mixtures of water and glycerin of low viscosity (3.5 cP and 8.5 cP) were used to displace tap water present in the test section with injection speeds of the mixture of 0.2 m/s, 0 .5 m/s and 1 m/s. Experimental data on glycerin mass fraction were collected from two sensors strategically positioned in the test section and compared with data taken from the simulations. The comparison between the experimental data and the simulation data allowed the validation of the SST Gamma – Theta turbulence model as the most suitable for the simulated conditions. From the analysis of the results, a stratified flow pattern was verified for the lowest injection speed of both mixtures. As for the cleaning time of the horizontal pipe, the mixture with a viscosity of 8.5 cP and 1 m/s was more effective, since the pipe cleaning took place in a shorter time. Thus, the case study achieved its objectives and the results were satisfactory, considering that it was possible to compare with data taken from the literature.